2001
DOI: 10.2307/3588029
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive Focus on Form in the ESL Classroom

Abstract: This article contributes to the growing body of descriptive research investigating focus on form, defined as the incidental attention that teachers and L2 learners pay to form in the context of meaningfocussed instruction. Whereas previous research addressed reactive focus on form (i.e., corrective feedback), the study reported in this article investigated preemptive focus on form (i.e., occasions when either the teacher or a student chose to make a specific form the topic of the discourse). The study found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
222
2
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(242 citation statements)
references
References 31 publications
16
222
2
2
Order By: Relevance
“…Mackey et al (2000) conducted an observational study which revealed that uptake occurred in more than half (52%) of all feedback episodes, a relatively high rate. Similarly, Ellis et al (2001a) found that learner uptake after incidental focus on form was generally high and successful in the immersion classrooms they examined. Similarly, Panova and LysterÕs (2002) observational study of the range and types of teacher feedback, and their relationship to learner uptake and immediate repair, found relatively high rates of learner uptake (47%) but rates of learner uptake with immediate repair were low in the examined classrooms (16%).…”
Section: Occurrence Of Uptake In L2 Classroomsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mackey et al (2000) conducted an observational study which revealed that uptake occurred in more than half (52%) of all feedback episodes, a relatively high rate. Similarly, Ellis et al (2001a) found that learner uptake after incidental focus on form was generally high and successful in the immersion classrooms they examined. Similarly, Panova and LysterÕs (2002) observational study of the range and types of teacher feedback, and their relationship to learner uptake and immediate repair, found relatively high rates of learner uptake (47%) but rates of learner uptake with immediate repair were low in the examined classrooms (16%).…”
Section: Occurrence Of Uptake In L2 Classroomsmentioning
confidence: 99%
“…There has been considerable research on uptake (Mackey et al 2000;Oliver 2000;Ellis et al 2001a;Panova and Lyster 2002;McDonough 2005). Some argue that learner uptake plays a positive role in learnersÕ second language development (McDonough 2005;Loewen 2005); others, even though they admit that uptake may be an important and observable source for understanding the impact of the feedback, doubt that it leads to long-term learning (Nabei and Swain 2002;Morris and Tarone 2003).…”
Section: Impact Of Uptake On Language Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Mackey et al (2000: 476) situate NfM at points of 'communication breakdown' and describe it as triggered by 'something incomprehensible [which] becomes the impetus for learners to recognize an inadequacy in their own rule system. ' For Ellis (1999: 3) it is a 'communicative impasse' which leads to NfM and similarly in Ellis et al (2001) negotiation is something which occurs after a signal that there is a linguistic problem which needs explicit resolution.…”
Section: The Role Of the Negotiation For Meaning In Slamentioning
confidence: 99%
“…Oliver 1995;Lyster 1998;Long et al 1998;Braidi 2002) and focus-on-form episodes that are available in whole class settings (e.g. Doughty and Varela 1998;Ellis et al 2001) and are often, although not always, initiated by a native speaker or teacher who has not encountered a communication failure, impasse, or breakdown, (i.e. who has understood what the non-native speaker meant) but who has chosen where some language focus would be most useful.…”
Section: The Role Of the Negotiation For Meaning In Slamentioning
confidence: 99%